Does gender diversity help teams constructively manage status conflict? An evolutionary perspective of status conflict, team psychological safety, and team creativity - Lee, Hun Whee; Choi, Jin Nam; Kim, Seongsu (Organizational behavior and human decision processes, 2018)
•We examine the mediated and moderated effect of status conflict on team creativity.•Status conflict affected team creativity by undermining team psychological safety.•Gender diversity mitigated the negative impacts of status conflict on team psychological safety and team creativity. Despite the recent development of the literature on status conflict, the reasons and the contingency of the effects of status conflict on team creativity remain unclear. In this study, we draw on an evolutionary perspective to theorize team psychological safety as an underlying mechanism and gender diversity asa critical boundary condition for understanding why and when status conflict is likely to hinder team creativity. We tested these theoretical hypotheses using a multimethod (field and scenario studies) and cross-cultural (Korean and North American samples) set of studies. The findings offer novel practical and theoretical insights into the joint influence of status conflict and gender diversity on team psychological safety and team creativity.